2016
DOI: 10.1016/j.joms.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eruption Status of the Mandibular Third Molar on Distal Caries in the Adjacent Second Molar

Abstract: Impaction depth and angulation of the MTM are associated with distal caries in the MSM. Angulation of the MTM is more stable and reliable than the CEJ distance between the distal MSM and the mesial MTM for the estimation of risk factors related to the MTM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
53
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 24 publications
9
53
1
4
Order By: Relevance
“…The influence of the contact point location between the second and third molars on the formation of second molar distal caries has been well documented in the literature, with similar findings to the ones of our sample (14,17). In our opinion, contact points below the CEJ are more difficult to clean, leading to higher plaque accumulation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The influence of the contact point location between the second and third molars on the formation of second molar distal caries has been well documented in the literature, with similar findings to the ones of our sample (14,17). In our opinion, contact points below the CEJ are more difficult to clean, leading to higher plaque accumulation.…”
Section: Discussionsupporting
confidence: 90%
“…Authors such as Kang et al (17) reported even higher figures (52%), probably due to the use of cone-beam computed tomography (CBCT) to diagnose caries. According to the present study, the prevalence of L2M distal caries ranges from 20.6 – 30.2%, confirming the findings reported by Özeç et al (14), in a Turkish population (20%), and van der Linden et al (32%) (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to previously reported data, 4 influence of N‐M3s on A‐M2 pathologies in this study appears to be weaker than the influence of I‐M3s. Although some researchers have shown that M2s adjacent to I‐M3s of different impact patterns (e.g., full bony I‐M3s or soft‐tissue I‐M3s) might suffer different risks for pathologies, 4 , 27 , 32 I‐M3s were not classified into different levels in this study. The main purpose of this preliminary study was to identify whether N‐M3s adversely affect A‐M2s.…”
Section: Discussionmentioning
confidence: 89%